2021
DOI: 10.1590/1413-812320212612.10622021
|View full text |Cite
|
Sign up to set email alerts
|

Pandemia da COVID-19: insatisfação com o trabalho entre professores(as) do estado de Minas Gerais, Brasil

Abstract: Resumo O objetivo deste artigo foi verificar a prevalência e fatores associados à insatisfação com o trabalho docente entre professores(as) da rede pública estadual de educação básica do estado de Minas Gerais durante a pandemia da COVID-19. Inquérito epidemiológico do tipo websurveys, realizado com esses(as) professores(as) entre agosto e setembro de 2020 via formulário digital. A variável dependente foi a satisfação com o trabalho durante a pandemia, sendo os(as) satisfeitos(as) a categoria de referência. Fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
2
0
6
Order By: Relevance
“…The results show that most of the respondents had a low level of job satisfaction, with 50.47%, being these percentages much higher than those found in other public workers in Peru where most of them had average job satisfaction, (Abarca Arias et al, 2021;Aliaga-Zamora et al, 2022;Holguin Morales & Contreras Camarena, 2020).This is a negative factor because it can influence job performance (Chen & Sun, 2009;Obi, 2009). (Chen & Sun, 2009;Obiunu & Yalaju, 2020;Sudiardhita et al, 2018) affecting the quality of public services (Hernández Junco et al, 2009).. During the COVID-19 pandemic, drastic changes were made in the way job functions were performed, generating dissatisfaction, discomfort (Silva et al, 2021), stress and burnout (Kitsios & Kamariotou 2021). Therefore, it is important during these situations to make improvements in job content and organizational characteristics in order to reduce burnout and job dissatisfaction among staff (Ibrahim et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The results show that most of the respondents had a low level of job satisfaction, with 50.47%, being these percentages much higher than those found in other public workers in Peru where most of them had average job satisfaction, (Abarca Arias et al, 2021;Aliaga-Zamora et al, 2022;Holguin Morales & Contreras Camarena, 2020).This is a negative factor because it can influence job performance (Chen & Sun, 2009;Obi, 2009). (Chen & Sun, 2009;Obiunu & Yalaju, 2020;Sudiardhita et al, 2018) affecting the quality of public services (Hernández Junco et al, 2009).. During the COVID-19 pandemic, drastic changes were made in the way job functions were performed, generating dissatisfaction, discomfort (Silva et al, 2021), stress and burnout (Kitsios & Kamariotou 2021). Therefore, it is important during these situations to make improvements in job content and organizational characteristics in order to reduce burnout and job dissatisfaction among staff (Ibrahim et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Diante dessa afirmativa, foi necessário, a partir do cenário pandêmico, fazer adequações no ambiente de trabalho para realizar as atividades não presenciais, conforme apontam os gráficos a seguir. exacerbado pela falta ou pelo acesso precário às novas tecnologias educacionais, não só intensificou a insatisfação profissional, como também aprofundou as desigualdades socioeducacionais no Brasil (Silva, 2022).…”
Section: Metodologiaunclassified
“…Moreover, understanding teacher’s experiences throughout the pandemic is of critical importance for the future of education. Multiple studies have indicated that teachers have experienced higher levels of dissatisfaction and a lower sense of success during the pandemic 37 41 , resulting in increased levels of attrition rates worldwide 42 .…”
Section: Introductionmentioning
confidence: 99%